MLA IN CRIMINAL MATTERS AS ASSET RECOVERY’S TOOL - Ahmad Sobari (Fakultas Hukum Universitas Gadjah Mada, 2014)
Indonesia has the Act No. 1 of 2006 Concerning Mutual Legal Assistance in Criminal Matters, and has ratified Treaty on MLA in Criminal Matters (ASEAN Treaty) with Act No. 15 of 2008, the act mandated to Ministry of Justice and Human Rights as the Central Authority. Modus operandi and crime increasingly sophisticated as technological developments, in such a way that cause difficulties to search, seize and transmit properties from the requested country to the requesting country, so that is needed bilateral or multilateral cooperation. Indonesia must be better cooperation among relevant agencies in accordance with established procedures. Indonesia memiliki Undang-Undang Nomor 1 Tahun 2006 tentang Bantuan Timbal Balik dalam Masalah Pidana dan meratifikasi Perjanjian tentang MLA in Criminal Matters (ASEAN Treaty)dengan UndangUndang Nomor 15 Tahun 2008, dan mandat kepada Kementerian Kehakiman dan Hak Asasi Manusia sebagai otoritas pusat. Modus operandi kejahatan makin canggih seiring perkembangan teknologi, sedemikian rupa yang menyebabkan kesulitan untuk mencari, menyita dan mengirimkan hasil kejahatan dari negara diminta kepada negara peminta, sehingga perlu kerjasama bilateral atau multilateral. Di Indonesia harus ada kerjasama yang lebih baik antar instansi terkait sesuai dengan prosedur yang ditetapkan.